Animal behavior frozen in time: gregarious behavior of Early Jurassic lobsters within an ammonoid body chamber. - Adiël A Klompmaker (Public Library of Science (PLoS), 2012)
Direct animal behavior can be inferred from the fossil record only in exceptional circumstances. The exceptional mode of preservation of ammonoid shells in the Posidonia Shale (Lower Jurassic, lower Toarcian) of Dotternhausen in southern Germany, with only the organic periostracum preserved, provides an excellent opportunity to observe the contents of the ammonoid body chamber because this periostracum is translucent. Here, we report upon three delicate lobsters preserved within a compressed ammonoid specimen of Harpoceras falciferum. We attempt to explain this gregarious behavior. The three lobsters were studied using standard microscopy under low angle light. The lobsters belong to the extinct family of the Eryonidae; further identification was not possible. The organic material of the three small lobsters is preserved more than halfway into the ammonoid body chamber. The lobsters are closely spaced and are positioned with their tails oriented toward each other. The specimens are interpreted to represent corpses rather than molts. The lobsters probably sought shelter in preparation for molting or against predators such as fish that were present in Dotternhausen. Alternatively, the soft tissue of the ammonoid may have been a source of food that attracted the lobsters, or it may have served as a long-term residency for the lobsters (inquilinism). The lobsters represent the oldest known example of gregariousness amongst lobsters and decapods in the fossil record. Gregarious behavior in lobsters, also known for extant lobsters, thus developed earlier in earth's history than previously known. Moreover, this is one of the oldest known examples of decapod crustaceans preserved within cephalopod shells.